Memorandum of Understanding between the Board of Trustees of the University of Illinois, United States of America and BRAC University, Dhaka, Bangladesh (2008) - University of Illinois; BRAC University (University of Illinois and BRAC University, 2013)
The Board of Trustees of the University of Illinois, on behalf of its campus in Chicago, Illinois, United States of America and BRAC University, Dhaka, Bangladesh, wishing to establish cooperative relations between the two institutions, especially to develop the academic and cultural interchange through mutual assistance in the areas of education and research.